A world in crisis : a marxist analysis for the 1990s : the resolutions and conclusions of the 6th world congress of the Committee for a Workers' International. - Committee for a Workers' International (CWI) (London : CWI, 1994)
Bibliotheek François Vercammen
Engels
Monografie